A Classification Approach with Machine Learning Methods for Technical Problems of Distance Education: Turkey Example - Yayla, Rıdvan; Yayla, Halime Nur; Ortaç, Gizem; Bilgin, Turgay Tugay (INT COUNCIL OPEN & DISTANCE EDUCATION, 2021)
Distance education is an education model in which the lessons can be taught simultaneously using technical material without time and space restrictions. It has gained importance after the Covid-19 pandemic processes and has been implemented as a valid educational model in all educational institutions. Due to the sudden pandemic measures, distance education has brought about a lot of technical problems at unprepared educational institutions against the pandemic. In this paper, a classification approach is proposed by machine learning methods on Twitter instead of the usual structured research methods such as survey, one-on-one meeting for technical problems of distance education. The most encountered and commented distance education problem, which can be defined in different languages by the proposed method, have been analysed with Turkey example. Sentiment analysis has been made from negative and neutral tweets about distance education. The problems have been classified by natural language processing methods based on Turkish word analysis.
Keywords: Classification; Covid-19; distance education; education technology; machine learning